2013 BRICS Congress on Computational Intelligence and 11th Brazilian Congress on Computational Intelligence 2013
DOI: 10.1109/brics-cci-cbic.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Used to Stator Winding Interturn Short-Circuit Fault Detection in an Induction Motor Driven by Frequency Converter

Abstract: This work is the application of a Multilayer Perceptron Artificial Neural Network (MLP ANN) to detect early interturn short-circuit faults in a three-phase converter-fed induction motor. The quantity used to analyze the problem is the stator current or, more specifically, the harmonic content of its frequency spectrum, also called current signature. The analysis through the current signature is a non-invasive method and may be embedded in the frequency converter, what is a great advantage. The dataset used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The proper performance of machine learning techniques in various studies led to the rapid development of the use of these methods in the science and industry related to power electronics. For the first time in 2013, a new machine learning technique called Extreme Learning Machine (ELM) has been proposed to predict the inter-turn SC fault in a three-phase converter-fed induction motor [33]. In the same study, in order to express the effectiveness of the suggested procedure, one of the ANN methods called MLP is also utilized to identify faults, which the results emphasize the superiority of the ELM method.…”
Section: B Literature Review Of Fault Detection In Pessmentioning
confidence: 99%
See 3 more Smart Citations
“…The proper performance of machine learning techniques in various studies led to the rapid development of the use of these methods in the science and industry related to power electronics. For the first time in 2013, a new machine learning technique called Extreme Learning Machine (ELM) has been proposed to predict the inter-turn SC fault in a three-phase converter-fed induction motor [33]. In the same study, in order to express the effectiveness of the suggested procedure, one of the ANN methods called MLP is also utilized to identify faults, which the results emphasize the superiority of the ELM method.…”
Section: B Literature Review Of Fault Detection In Pessmentioning
confidence: 99%
“…𝜃(𝑥) denotes the agent of a nonlinear mapping function. Computation SC Converter-fed induction motors [31] Rotor fault Converter-fed induction motor and changeable rotors [148] OC switch fault Three-parallel converters in a wind turbine [149] OC Proton exchange membrane fuel cell and DC-DC Converter [33] Intern-turn SC Three-phase converter-fed induction motor [ Mainly in solving most problems, it has a high dependence on the type of inputs. It is highly sensitive to complex and noisy data.…”
Section: ) Support Vector Machine (Svm)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the generator, some frequency components appear in the Fourier spectrum that may make it difficult to identify the normal conditions from the faults. De Oliveira [12] used the FT, based on the frequency spectrum theory of Penman [42], and managed to identify 67% of short circuit failures, in 1.4% of turns, in an electric motor, using a current sensor.…”
Section: Faults On Wind Turbinesmentioning
confidence: 99%